Investigating the interaction between Neisseria meningitidis and human FGFR1 - Alsuwat, Meshari (2022)
Neisseria meningitidis is one of the most common bacterial causes of meningitis. This organism colonises the nasopharyngeal epithelium of the upper respiratory tract, where it is considered to be a commensal species. It can subsequently traverse the nasopharyngeal epithelium and enter the bloodstream, which can lead to disease including sepsis and meningitis. To cause meningitis, N. meningitidis must further cross the blood–brain barrier (BBB) to reach the meninges. This requires it to first bind to endothelial cells in a process that is incompletely understood at present. However, previous reports have shown that epidermal growth factor receptor (EGFR) and fibroblast growth factor receptor 1 (FGFR1) might be involved.